International civil service : principles, Practice and Prospects - Goel, S.L (New Delhi, 1984)
International Civil Service deals with the rationale, philosophy and growth of internationalism followed by the discussion of genesis and growth of the International Civil Service analytically in the historical context.
Keywords: Civil service